Brain derived neurotrophic factor induction of N-methyl-D-aspartate receptor subunit NR2A expression in cultured rat cortical neurons. - Small, D; Murray, C; Mealing, G; Poulter, M; Buchan, A; Morley, P (1998)
N-methyl-D-aspartate (NMDA) receptor subunit expression changes during development and following injury in several brain regions. These changes may be mediated by neurotrophic factors, such as brain derived neurotrophic factor (BDNF). Exposure of cultured cortical neurons to BDNF (100 ng/ml) for 24 h produced a significant decrease in the NMDA-induced whole-cell currents sensitive to the NR2B subunit selective NMDA receptor antagonist, CP-101,606, suggesting a relative decrease in NR2B subunit expression. There was a significant increase in NR2A by Western blot analysis. Consistent with the electrophysiology and Western blot analysis, reverse transcriptase-polymerase chain reaction (RT-PCR) amplification revealed that BDNF caused a significant increase in relative NR2A subunit expression, a significant decrease in relative NR2B subunit expression and no change in relative NR2C subunit expression. These results suggest that BDNF enhances NMDA receptor maturation, warranting further study of the mechanism of BDNF effects on NMDA receptor subunit expression and the role these effects play in development and neuronal injury.